Hypoxia Stress Induces Tissue Damage, Immune Defense, and Oxygen Transport Change in Gill of Silver Carp (Hypophthalmichthys molitrix): Evaluation on Hypoxia by Using Transcriptomics - Li, Xiaohui; Ling, Chen; Wang, Qiaoxin; Feng, Cui; Luo, Xiangzhong; Sha, Hang; He, Guoyu; Zou, Guiwei; Liang, Hongwei (Frontiers in Marine Science, 2022)
The silver carp (Hypophthalmichthys molitrix) is an economically, as well as environmentally, important fish that harbors low environmental hypoxia tolerance and frequently contributes to a loss of aquaculture productivity. The gill is the first tissue attacked by hypoxia; however, the response of the gills of H. molitrix to hypoxia stress at the tissue, cellular, and molecular levels has not been clearly established. The influence of hypoxia on histological features along with gene expression in silver carp gills were explored in this research. The hematoxylin and eosin-stained sections and electron microscopy examinations of gills indicated that the gill lamellae were seriously twisted, gill filaments were dehisced, and the swelling and shedding of epithelial cell layer in the gill tissue were intensified along with the degree of hypoxia. In the hypoxia, semi-asphyxia, and asphyxia groups, the gill transcriptomic assessment of shifts in key genes, as well as modulatory networks in response to hypoxic conditions revealed 587, 725, and 748 differentially expressed genes, respectively. These genes are abundant in immune response signaling cascades (e.g., complement and coagulation cascades, Nucleotide-binding and oligomerization domain (NOD)-like receptor signaling cascade, and differentiation of Th1 along with Th2 cells) and oxygen transport [e.g., MAPK, PI3K-Akt, and hypoxia-inducible factor 1 (HIF-1) signaling cascades]. Genes linked to immune response (e.g., c2, c3, c6, klf4, cxcr4, cd45, and cd40) and oxygen transport (e.g., egln1, egln3, epo, ldh, and vegfa) were additionally identified. According to our findings, the silver carp may be using “HIF-1” to obtain additional oxygen during hypoxia. These findings illustrate that hypoxia stress might damage gill tissue, trigger an immunological response, and activate HIF-1 signaling to increase oxygen availability under hypoxic situations. The findings of this work will help scientists better understand the molecular mechanisms driving hypoxia responses in hypoxia-sensitive fish and speed up the development of hypoxia-resistant varieties.